A European public investment outlook - Cerniglia, Floriana; Saraceno, Francesco (Open Book Publishers, 2020)
The essays in this outlook collectively foster a broad approach to and definition of public investment, that is today more relevant than ever. Offering up a timely and clear case for the elimination of bias against investment in European fiscal rules, this outlook is a welcome contribution to the European debate, aimed both at policy makers and general readers